Association Between Kawasaki Disease and Childhood Epilepsy: A Nationwide Cohort Study in Taiwan - Lin, Chien-Heng; Lai, Jung-Nien; Lee, Inn-Chi; Chou, I-Ching; Lin, Wei-De; Lin, Mei-Chen; Hong, Syuan-Yu (Frontiers in Neurology, 2021)
Abstract (1) Background: Kawasaki disease is a common vasculitis of childhood in East Asia. The complications following Kawasaki disease mostly included cardiovascular sequelae; noncardiac complications have been reported but less studied. This study investigated potential epilepsy following Kawasaki disease in Taiwanese children.(2) Objectives: Through National Health Insurance Research Database, we retrospectively analyzed the data of children aged <18 years with clinically diagnosed Kawasaki disease from January 1, 2000 to December 31, 2012 in Taiwan. These patients were followed up to estimate the incidence of epilepsy in the Kawasaki cohort in comparison with that in the non-Kawasaki cohort in Taiwan. (3) Results: A total of 8,463 and 33,872 patients in the Kawasaki and non-Kawasaki cohorts were included in the study, respectively. Of the total eligible study subjects, 61.1% were boys and 38.9% were girls; most patients with newly diagnosed Kawasaki disease were aged <5 years [88.1%]. Patients with Kawasaki disease showed a higher incidence rate [47.98 vs. 27.45 every 100,000 person years] and significantly higher risk [adjusted hazard ratio = 1.66, 95% confidence interval = 1.13–2.44] of epilepsy than those without the disease. Additionally, female sex [adjusted hazard ratio = 2.30, 95% confidence interval = 1.31–4.04] and age <5 years [adjusted hazard ratio = 1.82, 95% confidence interval = 1.22–2.72] showed a significantly higher risk of epilepsy in the Kawasaki cohort.(4) Conclusion: Results revealed a higher incidence rate and significant risk of epilepsy in Taiwanese children with Kawasaki disease than in those without the disease. Therefore, children diagnosed with Kawasaki disease are recommended follow-up as they have a high risk of epilepsy and seizure disorders. Keywords: Kawasaki disease, Children, Epilepsy